Occupants’ Perception of Quality Design and Standard in Building Services for Effective Property Management - Oromidayo Thontteh, Esther; Olaopin Olanrele, Olusegun (International Journal of Property Sciences (E-ISSN: 2229-8568), 2015)
Building performance evaluation techniques are hardly applied to occupied premises in property management practice in Nigeria. It undermines occupiers’ satisfaction as well as occupiers’ perception and action toward facilities. Tenants’ decision to stay or leave a property and the reason for conflict of interest over rent increment could be adduced to poor service quality and dissatisfaction. The need to measure occupiers’/customers’ satisfaction in dwelling houses also arises because it is now universally accepted that users have become more astute and their rising expectations need to be met. The specific objective of the study is assessment of occupiers’ satisfaction using quality performance criteria under the SERVICE QUALITY DIMENSIONS in selected high-rise buildings. The study adopted a cross-sectional research design approach. The data were collected through the aid of questionnaire survey to investigate 54 quality service and property performance indicators and were analyzed quantitatively. 106 questionnaires were returned from the 207 tenants of the selected buildings representing 51.2% response rate. The mean item score (MIS) for satisfaction level for each indicator was calculated and expressed in percentages to arrive at importance index for the purpose of ranking in line with the highest derived satisfaction level of the respondents. The study found that tenants are highly dissatisfied with communication, and lack of interaction becomes a major reason for non-satisfaction of service quality. Out of 52 indicators, only 8 environmental indicators show no significant difference between expectation and perception. Tenants were least satisfied with communications, service management, water quality and cost. Property management service delivery in Nigeria is not customer/user driven with 44 out of 52 indicators having significant differences between tenant expectation and perception of service quality and delivery. The study recommends improvement in communication gap, definition of occupier’s service standards for adequate service delivery and reduction of unsatisfactory service designs and quality.